Platelets are highly efficient and efficacious carriers for tumor-targeted nano-drug delivery. (31st December 2022) - Li, Qi-Rui; Xu, Hua-Zhen; Xiao, Rong-Cheng; Liu, Yan; Tang, Jun-Ming; Li, Jian; Yu, Ting-Ting; Liu, Bin; Li, Liu-Gen; Wang, Mei-Fang; Han, Ning; Xu, Yong-Hong; et al.
Abstract: The present work aims to prove the concept of tumor-targeted drug delivery mediated by platelets. Doxorubicin (DOX) attached to nanodiamonds (ND-DOX) was investigated as the model payload drug of platelets. In vitro experiments first showed that ND-DOX could be loaded in mouse platelets in a dose-dependent manner with a markedly higher efficiency and capacity than free DOX. ND-DOX-loaded platelets (Plt@ND-DOX) maintained viability and ND-DOX could be stably held in the platelets for at least 4 hr. Next, mouse Lewis lung cancer cells were found to activate Plt@ND-DOX and thereby stimulate cargo unloading of Plt@ND-DOX. The unloaded ND-DOX was taken up by co-cultured cancer cells which consequently exhibited loss of viability, proliferation suppression and apoptosis. In vivo, Plt@ND-DOX displayed significantly prolonged blood circulation time over ND-DOX and DOX in mice, and Lewis tumor grafts demonstrated infiltration, activation and cargo unloading of Plt@ND-DOX in the tumor tissue. Consequently, Plt@ND-DOX effectively reversed the growth of Lewis tumor grafts which exhibited significant inhibition of cell proliferation and apoptosis. Importantly, Plt@ND-DOX displayed a markedly higher therapeutic potency than free DOX but without the severe systemic toxicity associated with DOX. Our findings are concrete proof of platelets as efficient and efficacious carriers for tumor-targeted nano-drug delivery with the following features: 1) large loading capacity and high loading efficiency, 2) good tolerance of cargo drug, 3) stable cargo retention and no cargo unloading in the absence of stimulation, 4) prolonged blood circulation time, and 5) excellent tumor distribution and tumor-activated drug unloading leading to high therapeutic potency and few adverse effects. Platelets hold great potential as efficient and efficacious carriers for tumor-targeted nano-drug delivery.